Preparation and characterisation of Silica-Coated Iron OxideNanoparticles (FesOa@SiOz-NPs) / Nurul Izza Taib, Famiza Abdul Latif and Nur Diyana Syazwani Zambri - Taib, Nurul Izza; Abdul Latif, Famiza; Zambri, Nur Diyana Syazwani (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
Iron oxide nanoparticles (Fe3 O4 -NPs ) were synthesized in ammonium hydroxide medium using neem leaf extract as a reducing agent through a co-precipitation method. SiO2 has been coated on the surface of Fe3 O4 (Fe3 O4 @SiO2 ) by hydrolysis and condensation of tetraethyl orthosilicate (TEOS) under alkaline medium conditions at 80oC. The properties of the resulting nanoparticles were analysed by transmission electron microscopy (TEM), fourier transform infrared (FTIR) field emission scanning electron microscopy (FESEM), energy-dispersive X-rays spectroscopy (EDX) and vibrating sample magnetometry (VSM). It was found that only500L TEOS was required to obtain the best coating on Fe3 O4 core structures. TEM micrographs show the formation of multiple cores of iron oxide nanoparticles within the silica matrix. FTIR analyses show the formation of Si-O-Si bonds at 1084.2-1101.4 cm-1 hence confirming that Fe O core was successfully coated by SiO2 . From FESEM analysis, the average size of silica was found to be ~ 50 -70 nm. EDX of the Fe3 O4 @SiO2 confirmed that silica had been successfully coated on the surface of Fe3 O4. VSM measurements revealed the superparamagnetic properties of Fe3 O4 @SiO2 that is desirable for biomedical applications.